2018
DOI: 10.1080/02713683.2018.1449220
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Optical Quality: Ocular Scattering and Aberrations in Eyes Implanted with Diffractive Multifocal or Monofocal Intraocular Lenses

Abstract: Both ocular scattering and wave-front aberrations play essential role in retinal image quality, which may be overestimated when only aberrations were taken into account. Combining the effect of ocular scattering with HOA will result in a more accurate assessment of the visual and optical quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…Nah-, mittel-und entfernungsabhängig am besten korrigierte Sehschärfe und unkorrigierte Sehschärfe wurden zu Beginn und 3 [1], considerable development has occurred in the field of intraocular lenses (IOLs) to correct a wider range of refractive errors and achieve better visual performance. Amongst the most researched properties are the capacities to achieve spectacle independence and optimal visual acuity regardless of focal lengths and light conditions, as well as the reduction of visual aberrations [2]. A wide range of designs and optical properties were developed in an attempt to achieve this, including refractive, diffractive, refractivediffractive, and apodized diffractive multifocal IOLs [3,4].…”
Section: Zusammenfassungmentioning
confidence: 99%
See 1 more Smart Citation
“…Nah-, mittel-und entfernungsabhängig am besten korrigierte Sehschärfe und unkorrigierte Sehschärfe wurden zu Beginn und 3 [1], considerable development has occurred in the field of intraocular lenses (IOLs) to correct a wider range of refractive errors and achieve better visual performance. Amongst the most researched properties are the capacities to achieve spectacle independence and optimal visual acuity regardless of focal lengths and light conditions, as well as the reduction of visual aberrations [2]. A wide range of designs and optical properties were developed in an attempt to achieve this, including refractive, diffractive, refractivediffractive, and apodized diffractive multifocal IOLs [3,4].…”
Section: Zusammenfassungmentioning
confidence: 99%
“…They are, however, known to produce a subnormal visual performance in the intermediate range, which, with the rise of computer use, can significantly impair a patientʼs quality of life [6,7]. Other common adverse outcomes of multifocal IOLs are visual aberrations and photic phenomena, including glares and halos, as well as a reduced contrast perception [2,8].…”
Section: Zusammenfassungmentioning
confidence: 99%
“…Some recent studies reported that significantly higher values of OSI and lower values of MTF cutoff and SR were found in the multifocal phakic eyes than monofocal IOL eyes and normal elder [41,42]. The diffractive or refractive rings in theoptics of multifocal IOLs may be partially responsible for causing scatter, resulting in moderate glare [41]. Thus, assessing the decision of laser capsulotomy after multifocal IOL implantation may require more other parameters.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of literatures [20,21,22] have reported that the decrease of retinal imaging quality after cataract phacoemulsi cation was closely related to the change of total ocular wavefront aberration. The changes of total aberrations of the whole eye after surgery were mainly related to the changes of wavefront aberrations of the anterior corneal surface and the changes of IOL wavefront aberrations of the replacement [23,24,25,26] .…”
Section: Discussionmentioning
confidence: 99%